Hospital admissions due to headaches in children and adolescents in Brazil: An ecological study from 2013 to 2023. - Cavagnoli, Giovanna Lourenço; Espindola, Vitor Dias; Messias, Emely Regina; Queiroz, Bruno Dias; Mendes, Natalia Camila Correia; Souza, Marcelo Alves de (Headache Medicine, 2024)
Introduction: Headaches are among the most common pains in childhood and are one of the reasons why most parents seek specialized neurological care. Objectives: To analyze the epidemiological profile of hospitalizations for headaches in children and adolescents in Brazil between 2013 and 2023. Method: Descriptive ecological study, through data collection by the SUS Hospital Information System (SIH/SUS), linked to the Department of Informatics of the Unified Health System (DATASUS) in may 2024. The number of hospital admissions due to headaches in the pediatric population, aged 0 to 19 years, in the period 2013-2023 was analyzed. The variables used were: Age group, gender, race, year of hospitalization, region, average value and average length of stay. Results: During the period analyzed, there were 17,924 children and adolescents hospitalized because of headaches. The Southeast region had the highest number of hospitalizations (35.8%, 6,423), and the year 2023 had the highest number of cases (2,092). Regarding sex/race, the analyses showed a higher prevalence of hospitalizations among females (62.3%, 11,166) with brown skin color (43.3%, 7,774) as the majority. The predominant age group was between 15-19 years (43.9%, 7,866). The average length of stay of hospitalizations was between 3 and 5 days, with a higher average for the age group under 1 year (5.9 days). The average value of hospitalizations was also higher in this population (1,833.84 reais), a value considered above the average of the pediatric age groups of around 691.39 reais. In relation to total expenditures, migraine in the pediatric population generated a total cost of 6,499,527.48 reais in the period analyzed. Conclusion: In view of the analyses, the epidemiological profile of hospitalizations was led by the age group of 15-19 years. Most of them are female, brown and residents of the state of São Paulo. Finally, biological and behavioral factors may be linked to the occurrence of headaches in children and adolescents, and public policies aimed at the prevention and treatment of this condition need to be adequate and improved.